Procedural sedation in dentistry with the use of dexmedetomidine: effects on clinical examples - Bohdan Mykhaylov (Медицина болю, 2023)
The presence of acute pain can be the worst negative impressions of a person. Therefore, it is necessary to ensure the control of acute pain for comfort and prevention of the formation of chronic pain syndrome intraoperatively. The development of a multimodal approach to the control of acute pain allows for shorter results. The more we use antinociceptive receptors for pain control, the more comfortable our patient feels. Alpha-2-adrenergic agonists (clonidine, dexmedetomidine) became a key part of the anesthesiologist’s recruitment in the perioperative period. The very selective infusion of dexmedetomidine on alpha-2a central and peripheral receptors and alpha-2c receptors allowed the drug to be more widely absorbed during procedural sedation. The need for more drugs for procedural sedation may be taken to the maximum possible comfort for the patient, the happy doctor and the anesthesiological team, the change in drug administration and the most likely awakening. To balance and satisfy the needs of the consumer to help the most practical way to achieve the goal of combinations of drugs and analysis of useful and negative effects.